(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Between September 1996 and October 1997 in Greece an extensive study of the Agromyzidae attacking cultivated vegetables in the field as well as in greenhouses was carried out. The following species were collected: Liriomyza strigata (Meigen), L. bryoniae (Kaltenbach), L. huidobrensis (Blanchard), L. trifolii (Burgess) and Chromatomyia horticola (Goureau). L. huidobrensis was found to be the most wide-spread, with higher populations than all the others; it was present in all the samples coming from different regions, attacking cultivated vegetables both in fields and in greenhouses. L. strigata and L. bryoniae have fewer hosts and they were found in lower populations than the previous species. L. strigata attacks leaves of tomato, bean, eggplant, cucumber and squash plant in Central and Southern Greece as well as the Oriental Aegean Islands. L. bryoniae infests tornato, bean, cucumber and okra in North Greece and in Cyclades lslands. L. trifolii was found only on bean and tomato leaves in Southern Greece and Crete. Finally Chr. horticola was found on tomato leaves in Attica and on eggplant leaves in the Western Coast of Greece.